Contradiction between Policy and Teacher Belief about Intercultural Approach to English Language Teaching in Indonesian Universities - Aulia, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Teacher belief about Intercultural Approach to English Foreign Language Teaching (EFLT) is central for its practical teaching and learning activities. Otherwise, intercultural communicative competence (IC) will not culminate in improved knowledge, skills, and attitudinal development. A linear consistency between what a policy constitutes and how teachers perceive, and act is fundamental for the pedagogy. However, such a harmony has not been exhaustively investigated on multiple-layered practices and actors. It is found that there exists contradiction on institutional and individual levels in understanding the the pedagogy. It is suggested that these teachers must be equipped with professional developmental activities involving reflexivity on both their own wisdom of practice and critical awareness to be integrated into intercultural teaching and learning activities.